Remembering Gunnar Kulldorff (1927–2015) - Pumputis, Dalius; Čiginas, Andrius (Lithuanian Journal of Statistics, 2021)
A short message is dedicated to professor Gunnar Kulldorff who was the founder of the Baltic-Nordic-Ukrainian Network on Survey Statistics, and the President of the International Statistical Institute.